Implementation of strategies and programs for breastfeeding, complementary feeding, and malnutrition of young children in Brazil: advances and challenges - Sonia Isoyama Venancio; Gabriela Buccini (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Abstract: Malnutrition in all its forms has risen on global agendas due to the recognition of its magnitude and consequences for a wide range of human, social, and economic outcomes. Implementing strategies and programs with the needed scale and quality is a major challenge. The Brazilian National Survey on Child Nutrition (ENANI-2019) pointed out several advances but numerous challenges. In this paper, we reflect on the implementation progress of breastfeeding, complementary feeding and young children malnutrition strategies and programs in Brazil and how existing challenges can be overcome through the lens of implementation science. First, we present a brief history of such programs. Second, we selected two breastfeeding initiatives to illustrate and reflect on common implementation challenges. In these case studies, we used the RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) framework to analyze the implementation and scaling up barriers and facilitators. We found common barriers related to unclear goals about the reach of programs, challenges in assessing effectiveness and fidelity/quality during the real-world implementation, discontinuation or lack of funding, and lack of monitoring and evaluation impacting the sustainability of programs. We also discuss the use of implementation science to achieve adequate nutrition by 2030 and present critical elements for successful scale implementation of nutrition programs based on global evidence. Despite the investment to implement different actions aimed at facing infant feeding and malnutrition, high-quality implementation research must become a priority to catalyze progress in Brazil.